PENGELOLAAN KEUANGAN PENDIDIKAN PADA MASA PANDEMI COVID-19 - maulana, icep (Journal of Management Review, 2025)
This writing was carried out to provide a descriptive analysis with a literature review or literature on financial management in educational institutions during the COVID-19 pandemic. Schools have a duty to manage finances properly based on the principles of financial management, namely the principles of accountability, efficiency, and transparency, so that the money that will be used can be used optimally. These principles are contained in the Government Regulation of the Republic of Indonesia Number 48 of 2008 concerning Education funding, namely the principles of justice, efficiency, transparency, and public accountability. The regulation also explains that these four principles are used in the school financial management process starting from planning, implementation, and supervision.